Linguistic and culturological analysis of religious texts - Ostashchuk, Ivan (Skhid, 2015)
The paper explores the religious and cultural inner form of such notions as 'sacred-holy site', 'altar-fires of sacrifice', 'semiotics-semantics-sign' with the help of the linguistic and culturological method, using the classic languages material and ancient tradition of ceremonial and cult practices. It is proved that objects in cultural or religious texts can converge by minor properties; their symbolic interchangeability, distinct associative pallet, referential remoteness, relatedness to different referential systems or space-time discontinuity often contravene unambiguous comprehension of the text, result in polyphony and hence multiple interpretations. It is noted that the linguistic and culturological method of analyzing religious and cultural texts has a weighty potential in religious studies and theological research.